A CONCEPTUAL FRAMEWORK FOR COLLABORATIVE PROBLEM-BASED LEARNING - AHMAD ZAINUDDIN, SHAZARIN (2015)
This study is initiated to investigate learning theories for problems based on the workplace. Pertaining to this, a framework is proposed for collaborative problem based learning; and a prototype called Collab2learn Discussion Board (DB) is developed as referred on the problem that there is no online discussion board for students to give feedback on specific comment during online discussions. This study explores learners' performance when using Collab2learn DB in particular at different genders (female and male), internship exposure (pre-internship and post-internship) at different learning synchronicities (synchronous and asynchronous), and feedback formats (textual and iconic). Research methodology has adapted prototyping methodology for the study, whereby phpmyadmin and MySQL were used to develop the prototype. Accessible through the network, learners' performances participated in the learning sessions were measured in terms of quality - Solutions Quality (SQ), confidence - Solutions Confidence (SC), quantity - Solutions Quantity (SK), and speed - Speed of Solutions Generation (SS).